CCR5 blockade inflames antitumor immunity in BAP1-mutant clear cell renal cell carcinoma. Issue 1 (5th May 2020) - Zhou, Quan; Qi, Yangyang; Wang, Zewei; Zeng, Han; Zhang, Hongyu; Liu, Zhaopei; Huang, Qiuren; Xiong, Ying; Wang, Jiajun; Chang, Yuan; Bai, Qi; Xia, Yu; et al.
Abstract : Background: Patients with BRCA1-associated protein 1 (BAP1)-mutant clear cell renal cell carcinoma (ccRCC) have worse prognosis. C-C chemokine receptor 5 (CCR5) plays an important role in ccRCC development and its expression is elevated in BAP1-mutant tumors. Methods: 533 patients with ccRCC from The Cancer Genome Atlas cohort and 797 patients with ccRCC from the Shanghai cohort were enrolled. In vitro and in vivo studies were conducted with human ccRCC tumors and murine tumor models. The association between BAP1 and CCR5 or its ligands was assessed by immunohistochemistry, flow cytometry, real-time PCR and ELISA. Survival was compared between different subpopulations of patients using Kaplan-Meier curve. Therapeutic effect of CCR5 blockade was validated using human ccRCC tumors and murine models. Results: Expression of CCR5 and its ligands were elevated in BAP1-mutant patients with ccRCC. High CCR5 expression was indicative of poor prognosis in BAP1-low group of patients. CCR5 blockade prolonged the survival of tumor-bearing mice, resulting in enhanced cytotoxicity of T cells and antigen presentation of dendritic cells but repressed immune checkpoint expression. CCR5 ligands could recruit CCR5 + regulatory T cells to the tumor microenvironment. Additionally, BAP1-mutant ccRCC tumor cells secreted CCR5 ligands, which increased programmed cell death ligand 1 expression. However, both processes could be inhibited by CCR5 blockade. Study limitations include the unclear impact of CCR5 expressed by other cell populations. Conclusions: CCR5 in BAP1-mutant ccRCC results in an immune-suppressive microenvironment. Targeting CCR5 could provide a potential therapeutic benefit for patients. Trial registration number: NCT01358721, CA209-009.